2014
DOI: 10.1093/jb/mvu040
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms for the p38-induced cellular senescence in normal human fibroblast

Abstract: We previously reported that TAK1, one of the mitogen-activated protein kinase kinase kinases (MAP3Ks), represses the transcription of the human telomerase reverse transcriptase (hTERT) gene in human cancer cells and induces cellular senescence in normal diploid human cells. On the basis of these results, we presumed a link between hTERT repression and the induction of cellular senescence. In this study, we identified the MAPK p38 as a downstream mediator of TAK1, which represses hTERT transcription. Further, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…It has been reported that p38 signaling pathway was associated with cellular senescence and p38 induced cellular senescence by suppressing the transcription of TERT in normal human fibroblasts. 29,30 Here, we also found that the expression of MMP-3 in CCH fibroblasts was significantly reduced by p38specific inhibitor SB203580 ( Supplementary Fig. S2), indicating the potential role of p38 in CCH.…”
Section: Enhanced Cellular Senescence In Cch Conjunctival Tissuessupporting
confidence: 59%
See 1 more Smart Citation
“…It has been reported that p38 signaling pathway was associated with cellular senescence and p38 induced cellular senescence by suppressing the transcription of TERT in normal human fibroblasts. 29,30 Here, we also found that the expression of MMP-3 in CCH fibroblasts was significantly reduced by p38specific inhibitor SB203580 ( Supplementary Fig. S2), indicating the potential role of p38 in CCH.…”
Section: Enhanced Cellular Senescence In Cch Conjunctival Tissuessupporting
confidence: 59%
“…Blocking p38 MAPK signaling in CCH fibroblasts by transfection of siRNA targeting p38, or treatment with the p38-specific inhibitor SB203580, reduced the number of SA-b-Gal-positive cells and increased cell viability, indicating or implying p38 MAPK signaling in the cellular senescence of CCH fibroblasts. Harada et al 30 revealed that p38 induced cellular senescence in normal human fibroblasts by suppressing the transcription of TERT. The p38 MAPK signaling might result in downregulation of TERT in the CCH group.…”
Section: Discussionmentioning
confidence: 99%
“…p38α is activated by a wide variety of environmental stresses or inflammatory cytokines and is involved in orchestrating cellular response to different signals. Activation of p38α by oxidative stress, in fact by reactive oxygen species (ROS), plays an important role in mediating cell death (Cai et al 2006; Harada et al 2014). For example, ROS-induced p38 activation was shown to inhibit tumorigenesis (Gutiérrez-Uzquiza et al 2012) or to play a role in the pathology of Alzheimer’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, HSV-1 has been shown to activate p38 mitogen-activated protein kinase (MAPK) in an ICP27-dependent manner (39,40). This kinase can downregulate telomerase activity by inhibiting hTERT transcription (41). Therefore, it is possible that optimal HSV replication relies on the appropriate timing of telomerase activity.…”
Section: Discussionmentioning
confidence: 99%